Development of control models for the planning of sustainable transportation systems. (June 2015) - Maheshwari, Pankaj; Kachroo, Pushkin; Paz, Alexander; Khaddar, Romesh
Highlights: Macroscopic model for sustainable transportation consisting of transportation, activity, and environmental systems. Dynamic modeling using predator prey techniques representing the dynamics of three independent states. Application of optimal control theory for policy design in the context of sustainability. Introduction of a systems and controls methodology to make investment decisions. Abstract: Planning of sustainable transportation systems requires integration of multiple systems while considering a holistic approach. A limited amount of research has been conducted that simultaneously considers all the transportation, economic activity, environmental and social effects. The proposed research envisages incorporating considerations related to sustainability and providing solutions to stakeholders in policy making. In this paper, a dynamic model for planning and development of sustainable transportation systems is presented. This is given by a system of three nonlinear differential equations representing the dynamics of the three independent states, namely, transportation, activity, and environmental systems. A policy scenario considering investment in energy efficient technologies and its effects on the states is discussed to assist making investment decisions. Optimal control techniques are used to design the controls. The results show that it is possible to formulate an optimal control to achieve the desired target. Numerical results, based on actual parameters, are presented to illustrate the long-term trends of the states. The methodology discussed in this paper will be helpful to decision makers in making optimal decisions. The contribution of this research work is the introduction of a systems and controls methodology to develop optimal policies for the design of sustainable systems.